Analysis of the Implementation of An Ethnoscience-Based Learning Approach in Elementary Science Education - Yosefina Uge Lawe; Fransiskus Xaverius Dolo; Alexander Uta (Postgraduate, University of Mataram, 2025)
Ethnoscience highlights local culture and wisdom as learning resources, making science education more meaningful. This study aims to analyze the implementation of an ethnoscience-based learning approach to assist teachers in improving the quality of science education in elementary schools in accordance with students' needs. The sampling technique used was purposive sampling, involving 4 elementary schools in Golewa Subdistrict, Ngada Regency. Data collection methods included interviews, document analysis, literature review, and questionnaires. The data were analyzed using a descriptive qualitative approach. Based on data analysis and discussion, the following conclusions were drawn: The implementation of ethnoscience-based learning in science education has not been fully adopted by teachers in the 4 schools due to limited access to reading materials, teaching modules, instructional media, and a lack of teacher training in ethnoscience-based instruction. There is insufficient policy support from both the government and schools. There is a lack of specific training programs for teachers on ethnoscience-based learning. 4) There are limited resources and minimal support from school policies. This study shows that the implementation of ethnoscience-based learning requires adequate skills and resources from teachers. Better support in the form of teacher training, provision of sufficient teaching tools and materials, and effective time management is essential to improve the quality of science learning in elementary schools in Golewa Subdistrict.